Behavioral Intention of Muslim Tourists towards Halal Tourist Destinations of Bangladesh - Jamil, Md. Abdullah Al; Bipasha, Sabikun Nahar; Yousuf, A S M; Abdullah, Md. (Goodwood Publishing, 2025)
Purpose: The study aims to explore the influence of key factors on Muslim tourists' behavioral intentions to visit halal tourism destinations such as Bangladesh. It also aims to develop a framework for understanding the motivation and satisfaction criteria that guide Muslim tourists in selecting destinations, contributing to sustainable tourism development. Research Methods: This descriptive study examines the relationship between influencing factors and Muslim tourists' behavioral intentions to visit halal tourism destinations. Using non-probability convenience sampling, data is collected from a sample of 300 respondents. The study employed a PLS-SEM approach to analyze the data and test the hypotheses. Results: The findings reveal strong positive correlations between the availability of halal food (HF) and halal accommodation (HA) facilities and Muslim tourists' behavioral intentions to visit halal tourism destinations. Conversely, the analysis indicates that there is no significant positive relationship between halal transportation (HT) and halal place (HP) and Muslim tourists' behavioral intentions to visit these destinations. Limitations: The study focuses on a small number of samples, and it considers a developing country, which does not represent the diverse Muslim tourists. It can be extended further using the samples of developed countries as well. Contribution: The research offers theoretical and managerial implications for tourism authorities and service providers aiming to cater to the needs of Muslim tourists while fostering sustainable tourism practices.